The Lemmatization of Loan Words in the isiNdebele–English isiHlathululi-imagama/Dictionary and Their Successful Incorporation into the Language - Mahlangu, Sponono (Lexikos, 2014)
Researchers in linguistic and lexicographic fields such as Nkondo (1987: 70) and Kamwangamalu (1997: 89) assert that no language is lexically self-sufficient. According to Jafta (1987: 127), the reason for this is because no perfectly homogenous language group exist. There is no living language that can survive without supplementing its vocabulary through borrowing from another or other language(s). Thus Aitchison (2001: 249) is of the view that language gradually transforms itself and it cannot remain unaltered. On the other hand the so called ’purists’ disapprove of such alterations because they view these transformations as a process of language corruption because they prefer coining which Mojela (2010: 702) termed indirect borrowing. This article proves and illustrates this notion as correct, especially in the case of African languages. The technical terms and vocabulary in social interaction is based on adjacent South African languages such as English and Afrikaans, which as official languages have inevitably cross-pollinated each other. Researchers also agree that one way of enriching language is through borrowing. The aim of this article is to show that borrowing does not only enrich a language, but it also causes language dilution especially in the case of languages that are less technologically advanced or do not yet function as official languages.